Electrochemical and electrochromic properties of bilayer polymer films prepared by electrochemical polymerization based on star-shaped thiophene derivatives. (3rd June 2019) - Yan, Shuanma; Dong, Yujie; Li, Weijun; Chen, Lan; Dai, Yuyu; Ren, Ning; Wu, Yizhao; Zhang, Yujian; Zhang, Cheng
Abstract : Electrochemical and EC properties of bilayer films prepared by electropolymerization prove that charge-transport has important effects on switching speed of materials. Abstract : Two bilayer polymer films (pTPAT/pPHT and pPHT/pTPAT), derived from two star-shaped thiophene derivatives (TPAT and PHT) with central cores of triphenylamine and phenyl respectively, were successfully fabricated on ITO-glasses by electrochemical polymerization. The difference between the two bilayer polymer films pTPAT/pPHT and pPHT/pTPAT is just the layer configuration due to different sequential deposit orders of the pPHT and pTPAT layers during the electrochemical polymerization process. In the systems of bilayer films, the pPHT layer shows no electrochromism, a low HOMO level and a high impedance value, while the pTPAT layer shows obvious electrochromism, a high HOMO level and a low impedance value in contrast. The electrochromic properties showed that the optical contrast and cyclic stability of bilayer films are similar to those of the single pTPAT films, while the switching rate is relatively slower. Furthermore, in comparison with the pTPAT film, a higher ion-diffusion resistance was found in the bilayer film pTPAT/pPHT, and an obvious interface resistance was observed in the bilayer film pPHT/pTPAT. The existence of the pPHT layer in bilayer films may serve as a charge transport barrier and hinder the ion-diffusion or hole-injection process, depending on the layer structural arrangement in bilayer films. The investigation of the electrochromic properties of two bilayer films also provides unambiguous evidence for a fact that both ion-diffusion and charge-injection processes exerted great influences on the electrochromic switching rate of a polymer.